MESODIENCEPHALIC MODULATION – AN EFFECTIVE METHOD FOR THE TREATMENT OF GLOSSALGIA: CLINICAL OUTCOMES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The study examines the clinical efficacy of mesodiencephalic modulation (MDM) in the treatment of glossalgia, a disorder characterized by persistent pain and paresthetic sensations in the absence of structural tissue alterations. The method is based on targeted impulse stimulation of mesodiencephalic brain structures, aimed at correcting autonomic dysregulation, neurohumoral imbalances, and psychoemotional disturbances. The study included patients with various forms of glossalgia who underwent a 13-session course of MDM therapy using the "MDM-2000/1" device. Clinical assessment encompassed the evaluation of pain intensity, autonomic function, psychoemotional status, and systemic physiological markers. Post-treatment analysis demonstrated a statistically significant reduction in pain and paresthetic sensations, improved autonomic balance, and normalization of psychoemotional parameters. Objective measurements, including heart rate variability, hemoglobin concentration, oxygen saturation, and immune response markers, confirmed the systemic impact of MDM therapy. The absence of severe adverse reactions and high therapeutic efficacy substantiate the clinical relevance of MDM therapy in the management of glossalgia.